Electrophysiological Studies Revealed CaM1-Mediated Regulation of the Arabidopsis Calcium Channel CNGC12 - Zhang, Zhengli; Hou, Congcong; Tian, Wang; Li, Legong; Zhu, Huifen (Frontiers in Plant Science, 2019)
Arabidopsis cyclic nucleotide-gated channel (CNGC) family consists of 20 members, which has been reported to participate in various physiological processes, such as pathogen defense, development, and thermotolerence. Although CNGC11 and CNGC12 have been identified a decade ago and their role in programmed cell death is well studied, their precise channel regulation has not been studied electrophysiologically. Here, we determined the channel activities of CNGC11 and CNGC12 utilizing the two-electrode voltage-clamp technique in the Xenopus laevis oocyte heterologous expression system. Our results suggest that CNGC12 but not CNGC11 functions as an active calcium channel. Furthermore, the cNMPs did not affect the activities of CNGC11 nor CNGC12 in Xenopus oocytes. Interestingly, while the activity of CNGC11 was not affected by co-expression with CaM, the activity of CNGC12 was significantly enhanced when CaM1 was co-expressed in oocytes. This study reveals that the channel activities and the mechanisms of regulation by CaM are different between CNGC11 and CNGC12.